Association Between Platelet Levels and 28-Day Mortality in Patients With Sepsis: A Retrospective Analysis of a Large Clinical Database MIMIC-IV - Wang, Danni; Wang, Suning; Wu, Hao; Gao, Jiansheng; Huang, Kairong; Xu, Danhong; Ru, Huangyao (Frontiers in Medicine, 2022)
Background: This research focused on evaluating the correlation between platelet count and sepsis prognosis, and even the dose-response relationship, in a cohort of American adults. Method: Platelet counts were recorded retrospectively after hospitalization for patients admitted to Beth Israel Deaconess Medical Center's intensive care unit between 2008 and 2019. On admission to the intensive care unit, sepsis patients were divided into four categories based on platelet counts (very low <50 x 109/L, intermediate-low 50 x 109 to 100 x 109/L, low 100 x 109 to 150 x 109/L, and normal ≥150 x 109/L). To estimate platelet counts according to baseline platelet count the risk of sepsis 28-day mortality, a multivariate Cox proportional risk model was utilized, and a two-piecewise linear regression model was constructed to figure out the threshold effect. Results: The risk of 28-day septic mortality was nearly twofold higher in the platelet very low group compared to the low group (hazard ratios [HR], 2.24;95% confidence interval [CI], 1.92-2.6). Further analysis revealed a curvilinear association between platelets and the sepsis risk of death, with a saturation effect predicted at 100 x109/L. When platelet counts were below 100 x109/L, the risk of sepsis 28-day death decreased significantly with increasing platelet count levels (HR, 0.875; 95% CI, 0.84-0.90). Conclusion: When Platelet count was less than 100 x109/L, it was a strong predictor of the potential risk of sepsis death, which declined by 13% for every 10 x109/L growth in platelets. When platelet counts reach up to 100 x109/L, the probability of dying to sepsis within 28 days climbs by 1% for every 10 x109/L increase in platelet count.